The stability of short-term interest rates pass-through in the euro area during the financial market and sovereign debt crises - Avouyi-Dovi, S.; Horny, G.; Sevestre, P. (Journal of Banking & Finance, 2017)
We analyse the dynamics of the pass-through of banks’ marginal cost to bank lending rates over the 2008 crisis and the euro area sovereign debt crisis in France, Germany, Greece, Italy, Portugal and Spain. We measure banks’ marginal cost by their rate on new deposits, contrary to the literature that focuses on money market rates. This allows us to account for banks’ risks. We focus on the interest rate on new short-term loans granted to non-financial corporations in these countries. Our analysis is based on an error-correction approach that we extend to handle the time-varying long-run relationship between banks’ lending rates and banks’ marginal cost, as well as stochastic volatility. Our application is based on a harmonised monthly database from January 2003 to October 2014. We estimate the model within a Bayesian framework, using Markov Chain Monte Carlo methods (MCMC).We reject the view that the transmission mechanism is permanent over time. The long-run relationship moved with the sovereign debt crises to a new one, with a slower pass-through and higher bank lending rates. Its developments are heterogeneous from one country to the other. Impediments to the transmission of monetary rates depend on the heterogeneity in banks marginal costs and therefore, its risks. We also find that rates to small firms increase compared to large firms in a few countries. Using a VAR model, we show that overall, the effect of a shock on the rate of new deposits on the unexpected variances of new loans has been less important since 2010. These results confirm the slowdown in the transmission mechanism.